Experimental investigation of the discharge and thermal characteristics of an alternating current dielectric-barrier discharge plasma reactor. (25th November 2022) - Zhao, Qijin; Mao, Baoquan; Bai, Xianghua; Zhao, Junyan; Chen, Chunlin; Zhang, Xinxi; Wei, Shuguang; Gao, Qiang
Graphical abstract: Highlights: Thermal characteristics of a DBD reactor are investigated experimentally. Q – V Lissajous figures and calorimetry are utilized to analyze experiment results. Impacts of various factors on discharge and thermal characteristics are discussed. Physical mechanisms of variations of these characteristics are explored. Abstract: Dielectric-barrier discharge (DBD) plasma reactors offer significant prospects for use in various applications, such as for promoting the anti-icing or deicing of aircraft surfaces and for assisting combustion in ramjet engines. However, the discharge and thermal characteristics of DBD reactors, which are important factors affecting the process for optimizing the electrical parameters of these reactors, remain poorly understood. The present work addresses this issue by experimentally investigating the effects of various applied peak-to-peak voltages V pp, frequencies f h, airflow velocities u 0, and input airflow temperatures T in on the discharge power P d (0 <  P d  < 1200 W), thermal power P a, and thermal efficiency η of a DBD plasma reactor. The value of P d is determined according to the characteristics of Lissajous figures and the value of P a is determined according to the results of a rigorous calorimetry method. The results demonstrate that P d and η increase with increasing V pp owing to corresponding increases in the degree of ionization and the kinetic energy of the electrons in the discharge region. The values of P d and P a exhibit inverted V-shaped trends that initially increase with increasing f h up to the resonance frequency of the reactor, and then decrease with further increasing f h, while the value of η increases monotonically with increasing f h . In addition, the values of P d and P a exhibit similar inverted V-shaped trends with increasing u 0 because increasing u 0 initially improves the uniformity of the discharge, while further increases result in an increasing proportion of active gas constituents being moved out of the discharge region. The value of η, however, decreases with increasing u 0 . Finally, the values of P d, P a, and η increase with increasing T in, which is due to the resulting increase in the kinetic energy and frequency of collisions between active particles. Accordingly, the results of this study provide theoretical guidance for the optimal design of DBD plasma reactors used in various applications.